Islamic Leadership Training Based on The Characteristics of The Prophet's Leadership At SDN Bumi Waras Bandar Lampung - Rusdiani, Atik; Rahman, Bujang; Hariri, Hasan; Sari, Siti Rahma; Efendi, Ujang; Triyantoro, Joko; Farha, Syahla Athiya; Andarin, Marsanda; Wahyudienie, Mentari Bela (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2026)
This community service activity aimed to develop quality human resources for principals and teachers, as well as to increase the frequency of honesty, trust, wisdom, and effective communication in carrying out their duties. To strengthen principals and teachers' human resources, we provided insight, knowledge, and leadership preparedness based on the Prophet Muhammad's leadership approach. The specific aim was for participants to be able to use the Prophet Muhammad's leadership style.To achieve the aims and targets, the following methods were used: (1) lectures and discussions/questions and answers on the importance of understanding instructional leadership, (2) presenting educational leadership material, specifically instructional leadership, (3) providing training by presenting material through direct face-to-face meetings about instructional leadership, (4) providing instructional leadership training, and (5) conducting pre- and post-tests. This activity's aims were principals and teachers at SDN Bumi Waras Bandar Lampung. The desired objective was to be able to execute the Prophet Muhammad's leadership style and related technical matters in order to improve school education quality